1999
DOI: 10.1002/j.2168-9830.1999.tb00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing A Motivational Freshman Course In Using The Principle Of Attached Learning*

Abstract: This paper describes the development of a new, team‐taught, interdisciplinary, design‐oriented, introduction to engineering course that plays a role in the retention efforts of the engineering programs at our university. While the primary purpose of the new course has not changed from its original purpose, i.e., to introduce students to engineering as a field of study, the goals have been expanded to include motivating experiences to increase student retention. We discuss the rationale for the new course, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…These courses may vary in duration from portions of a semester to two-semester sequential modules. The course content and format also range from seminar-style classes to help students develop study skills and generate an enthusiasm for engineering [6]; courses primarily focused on particular technical skills such as computing or graphics; courses that expose students to the different engineering disciplines and functions, often as a path for choosing a specific major [4], [6]; courses that cover the professional practices related to a specific engineering discipline [3], [7]- [8]; courses that include an early exposure to design involving hands-on projects [9]- [10]; and courses that incorporate several essential engineering skills [11]. The type of implementation of introductory courses is usually geared to suit the needs of the particular program.…”
Section: Introductionmentioning
confidence: 99%
“…These courses may vary in duration from portions of a semester to two-semester sequential modules. The course content and format also range from seminar-style classes to help students develop study skills and generate an enthusiasm for engineering [6]; courses primarily focused on particular technical skills such as computing or graphics; courses that expose students to the different engineering disciplines and functions, often as a path for choosing a specific major [4], [6]; courses that cover the professional practices related to a specific engineering discipline [3], [7]- [8]; courses that include an early exposure to design involving hands-on projects [9]- [10]; and courses that incorporate several essential engineering skills [11]. The type of implementation of introductory courses is usually geared to suit the needs of the particular program.…”
Section: Introductionmentioning
confidence: 99%
“…For freshman in particular, it has been reported that the level of student integration into the college environment affects their ability to persist in the pursuit of a degree [8]. The multi-level experience is an attempt to create an environment in which students can interact academically and socially [9].…”
Section: Pedagogymentioning
confidence: 99%
“…We believe that many of those who left engineering after the first year would have continued in engineering if they had a more encouraging, helpful, personal, and stimulating first year experience. Many other universities have recognized the importance of the first year experience as well and have revamped their first year introductory engineering course(s) [1][2][3][4][5]. The goals of this introductory course are to provide students with basic skills for success, to enhance their interest in engineering and to cultivate their sense of belonging.…”
Section: Retention Of Freshman Studentsmentioning
confidence: 99%